2008
DOI: 10.3182/20080706-5-kr-1001.00695
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic synthesis of dependable logic controllers

Abstract: This paper presents an algebraic method to synthesize control laws for logical system controllers. The starting point is a set of functional and dependable requirements expressed with algebraic relations or state models. We propose to synthesize control laws by solving a Boolean equation which represents all the requirements. The mathematical results that we have obtained allow to establish the exact form of the solutions if this equation has solutions. The first step of this method is the formalization of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The second step consists in checking the consistency of the set of requirements by symbolic calculation. The sufficient condition for checking this consistency has been given in [20] but no strategy has been proposed for coping with potential inconsistencies. In this paper we show that thanks to new theorems the causes of these inconsistencies can be pointed out.…”
Section: Overview Of Our Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second step consists in checking the consistency of the set of requirements by symbolic calculation. The sufficient condition for checking this consistency has been given in [20] but no strategy has been proposed for coping with potential inconsistencies. In this paper we show that thanks to new theorems the causes of these inconsistencies can be pointed out.…”
Section: Overview Of Our Methodsmentioning
confidence: 99%
“…To prove Step (b), it is sufficient to substitute the expression for from (21) into (18) and to use (20) as follows:…”
Section: Theorem 11 (Solution Of a Single-unknown Equation) The Boolmentioning
confidence: 99%
“…This step is performed by solving the system of equations which represents the set of consistent requirements. The mathematical results we have obtained (Theorem 2 recalled in Section 4.2), allow to find a symbolic expression of the set of solutions under the form of a parametric expression (Hietter et al (2008b)). …”
Section: Overview Of Our Methodsmentioning
confidence: 99%
“…In a previous paper [3], we used our approach to synthesize the whole control law of a sequential system. We showed that different formalisms (such as finite states machines, logical expressions, timing diagrams, .…”
Section: Introductionmentioning
confidence: 99%
“…The choice of a control law in this space can be done by using an optimization criterion. In [3] we showed how to choose the most dependable control law.…”
Section: Introductionmentioning
confidence: 99%